Penanganan Kerusakan Clinker Berbasis Risiko Saat Pemuatan yang Dilakukan oleh Tenaga Bongkar Muat PT. Varia Usaha Bahari di Terminal Khusus PT. Semen Indonesia Tuban - Agil Fadila; Trisnowati Rahayu; Diyah Purwitasari (Pusat Riset dan Inovasi Nasional, 2024)
The problem of clinker damage during the loading process, many problems that arise cannot be separated from several natural factors and errors in procedures during the loading and unloading process. The aim of this research is to determine the impact, causes and efforts to prevent clinker damage during loading activities at the PT Special Terminal. Semen Indonesia Tuban. The research method used is a qualitative descriptive research method. This research was carried out at PT. Varia Usaha Bahri Tuban branch. The techniques used in collecting data are through observation, interviews and documentation. The results of this research are that the occurrence of clinker damage is the fault of the loading and unloading workers (TKBM) in maintaining the cleanliness of organic and inorganic waste in the stacking yard area and the foreman must carry out weather observations.